ChemInform Abstract: One‐Pot, Three‐Component Synthesis of Novel 4‐Phenyl‐2‐[3‐(alkynyl/alkenyl/aryl)phenyl]pyrimidine Libraries via Michael Addition, Cyclization, and C—C Coupling Reactions: A New MCR Strategy. Issue 17 (4th April 2013) - Reddy, L. Srinivasula; Reddy, T. Ram; Reddy, N. C. Gangi; Mohan, Reddy Bodireddy; Lingappa, Y.
Abstract Phenyl‐substituted pyrimidines, prepared in situ via Michael addition, cyclization, isomerization, and dehydration, undergo Pd‐catalyzed couplings to give the required medicinal scaffolds.